Effect of ultrasonic treatment on peanut protein isolate‐oat dietary fibre mixture gels induced by transglutaminase. (25th October 2020) - Niu, Xi; Zhao, Chengbin; Shi, Qiankun; Wang, Siqi; Zhao, Yilin; Li, Sheng; Yin, Huanhuan; Lin, Nan; Liu, Jingsheng
Summary: The effects of ultrasonic treatment on the physicochemical properties of transglutaminase‐induced gels prepared by the mixture of peanut protein isolate (PPI) and oat dietary fibre (ODF) were investigated. The gel strength and water holding capacity (WHC) of PPI gels and PPI‐ODF mixture gels were enhanced after ultrasonic treatment, and ultrasonic PPI‐ODF mixture gels had higher gel strength and WHC than ultrasonic PPI gels. The ultrasonic treatment of mixture gels increased the storage modulus, loss modulus and the relative percentage of immobilised water, which formed more continuous and compact gel microstructure, especially ultrasonic treated mixture gel prepared by PPI and 9% of ODF. The decrease of α‐helix and the increase of β‐sheet and random coil were caused by ultrasonic treatment, which improved the gel strength and WHC of PPI‐ODF mixture gels. The results indicated that the ultrasonic treatment would be an effective method for improving gelation properties of PPI‐ODF mixture. Abstract : The formation of peanut protein isolate‐oat dietary fibre mixture gels with ultrasonic treatment